Effectiveness of ABLS_R in developing visual performance for people with autism spectrum disorder. - Asmani, Rachida (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
The current study aimed to identify the effectiveness of Language and learning Skills Assessment program (Ablls-R) in developing visual performance for people with autism spectrum disorder. The study was conducted on a sample of children with autism spectrum disorder who are present at the Psychological and Pedagogical Center in Jalabin, Boumerdes Province. It consisted of (6) children in the age group (4-7) years, who were deliberately selected. The visual performance scale was applied to them, which is the second field of the (ABLLS-R) program. Therefore, the method used is the semi-experimental approach (pre-measurement and post-measurement). After analyzing the results, we reached the following: - There are statistically significant differences between the mean scores of the sample children in the pre and post measurement on the visual performance test in favor of the post measurement.- There are statistically significant differences between the mean scores of the respondents in the pre and post measurement on the visual performance test, according to the variable of intelligence level.Therefore, the role of intelligence can be emphasized as an important variable in obtaining effective results of the IPLES program in the development of visual performance in children with autism spectrum disorder, as children with high intelligence have a quick response to the learned experiences, and interact in a short time with the activities included in the program compared to children with limited intelligence, where their response is slower and their interaction and comprehension of programmed activities is less.